Do analógico ao digital: as transformações na produção dos instantâneos fotográficos do cotidiano - Araújo, Camila Leite de (2010)
The analog photo album allows us a memory of a past, within those archives we keep the picture of our beloved ones and the moments that we socially choose to represent us. Digital cameras, on the other side, provide an extensive photographic production which results in differentiated postures before the camera and extensive digital archives. One consequences of this visualization of existence is the constant recording of intimate moments, while the young legitimized digital photography as their tool of identity and communication, both featuring themselves and the contemporary image as transience and hybridity. Therefore, the contemporary is characterized by heterogeneous images with visual styles not classified topologically. Furthermore, with the digital technology arose the social virtual communities like facebook, orkut, fotolog and flickr expanded more the complexity of the process and began to exhibit the private moments in a public space. Mitchell (2005) brought to the scientific discourse which deals with imagery and text, the term “Pictorial Turn”, arguing that the images around us transform not only the world and identities, but have an increasingly important role in the construction of the social reality. This determines that the snapshot should not be understood as a mere repetition and recycling of past models, but has to deal with new issues emerging from contemporary process of negotiation and contestation, representation of the senses and pleasure. In an attempt to understand the transformations that the snapshots suffered from the transition from analog to digital, and thus understand the specific materials, aesthetic and social aspects of digital and analog photographic act, we performed a comparative analysis between two family albums: one analog and one digital.